Validating intrinsic capacity to measure healthy aging in an upper middle-income country: Findings from the ELSI-Brazil - Márlon J.R. Aliberti; Laiss Bertola; Claudia Szlejf; Déborah Oliveira; Ronaldo D. Piovezan; Matteo Cesari; Fabíola Bof de Andrade; Maria Fernanda Lima-Costa; Monica Rodrigues Perracini; Cleusa P. Ferri; Claudia K. Suemoto (Elsevier, 2022)
Summary: Background: While efforts have been made to validate intrinsic capacity (IC) as a multidimensional indicator of healthy aging in high-income countries, we still need evidence from lower-income countries. We examined associations of IC with wide ranges of activities of daily living in a nationally representative sample of Brazilians aged≥50 years. Methods: This cross-sectional analysis included 7175 participants from the Brazilian Longitudinal Study of Aging. IC domains (cognitive, psychological, sensory, locomotor, and vitality) were determined using self-reported and physical performance measures. IC was operationalized through factorial analysis. We investigated associations of IC and its domains with functional ability in basic, instrumental, and advanced activities of daily living (ADL, IADL, and AADL) using logistic regressions adjusted for sociodemographic, clinical, and modifiable risk factors. Findings: The IC bi-factorial model revealed satisfactory goodness-of-fit. Preserved ability in ADL and IADL, respectively, ranged from 69% and 29% to 89% and 74% across IC quartiles. In adjusted analyses, every standard deviation increment in IC composite score was associated with almost twice the odds of preserved ADL (OR=1·72; 95%CI=1·54-1·93), preserved IADL (OR=1·95; 95%CI=1·77-2·16), and high performance in AADL (OR=1·79; 95%CI=1·59-2·00). Similar results were reported using the IC domains as predictors. Although age, race/ethnicity, and education did not modify associations of IC with functional ability, we found sex differences with stronger relationships of IC with preserved ADL or IADL in females. Interpretation: Our results support IC validity and reliability to measure healthy aging in diverse socioeconomic and cultural settings. Incorporating IC in routine practices can promote holistic and person-centered care approaches in aging societies. Funding: The Brazilian Ministry of Health and Ministry of Science, Technology, Innovation, and Communication.